PERBANDINGAN HASIL GETAH ANTARA JELUTUNG KAPUR (Dyera lowii Hook.F) DAN JELUTUNG SANAMAN (Dyera costulata) DI HUTAN RAWA GAMBUT KALAMPANGAN (Comparison the Latex Yields Between Jelutung Kapur (Dyera lowii Hook.F) and Jelutung Sanaman (Dyera costulata): Lies Indrayanti and Nursiah - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACT Jelutung kapur (Dyera lowii Hock) and jelutung sanaman (Dyera costulata) are species that grow well at the peat swamp forest in Canal of Taruna, Kalampangan, Palangka Raya City. Aim of this research was to compare the latex yield between jelutung kapur (Dyera lowii Hock) and jelutung sanaman (Dyera costulata) at the peat swamp forest in Kalampangan. The research was done using factorial design with two factors, i.e. peat thickness (4 m and 5 m) and diameter class of the trees. Variables of the research were diameter (dbh) and height of 24 jelutung kapur and 18 jelutung sanaman. Data were collected each month as long as 11 months with considering the weather condition, i.e. precipitation and temperature. Research result show that there is irreversibility between precipitation vs temperature to latex yield. The more of precipitation so the higher of temperature that cause the reduction of latex yield. According BNT test, the highest latex yield is gotten from jelutung kapur with diameter class of >24 cm that grow at the site with the thickness of 4 m, meanwhile the lowest latex yield is gotten from jelutung sanaman with diameter class of < 24 cm that grow at the site with the thickness of 5 m. Average latex yield of jelutung kapur is 363,63 ml/extract/tree/month. Keywords: Diameter class, latex yield, peat thickness, precipitation, temperature.